2021
DOI: 10.1007/s00109-021-02111-0
|View full text |Cite
|
Sign up to set email alerts
|

Predisposition to Graves’ disease and Graves’ ophthalmopathy by genetic variants of IL2RA

Abstract: Previous studies have identified that Th17/Treg cells were involved in the occurrence and development of Graves' disease (GD). This study aimed at clarifying the association between GD susceptibility and nine single nucleotide polymorphisms (SNPs) of Th17/Treg cell-related genes, including IL2RA, miR27a, miR182, and FoxO1. A two-stage association study was performed in 650 GD patients and 1300 healthy controls. PCR-RFLP assays, real-time PCR, and ELISA were performed. In the first stage, association analysis h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…These results contrast with other discordant findings, where no associations between IL-2Rα SNPs and the presence of AITD were found [ 147 , 148 , 149 , 150 , 151 ].…”
Section: Genetic Factorscontrasting
confidence: 99%
“…These results contrast with other discordant findings, where no associations between IL-2Rα SNPs and the presence of AITD were found [ 147 , 148 , 149 , 150 , 151 ].…”
Section: Genetic Factorscontrasting
confidence: 99%
“…It has been reported that CD 25/rs2104286 (case/control: 650/1300; AA genotype: p = 8.772 × 10 −6 , OR = 1.636; A allele: p = 0.004, OR = 1.322) confers to GD susceptibility in the Chinese Han population ( Du et al, 2021 ). The minor allele A (case/control: 1474/1609, p = 0.00017, OR = 1.43) of rs41295061 and the homozygous AA genotype (case/control: 1474/1609, p = 0.0053, OR = 1.54) of rs11594656 conferred susceptibility to GD in a Russian population ( Chistiakov et al, 2011 ).…”
Section: The Genetic Pathogenesis Of Gdmentioning
confidence: 99%
“…Looking into the genetics, thyroid disorders are considered polygenic and result from the interaction of many genetic variants. A wide range of genes are known to be involved in thyroid dysfunctions, some with hyperthyroidism ( HLA-DR3 , CTLA4 , PTPN22 , CD40 , IL2RA , and FCRL3 ) and others with hypothyroidism ( SLC5A5 , SLC26A4 , TG , TPO , DUOX2 , and DUOXA2 ) (Bufalo et al, 2021; Du et al, 2021; Geysels et al, 2022; Khong et al, 2016; Li et al, 2020; Peters et al, 2019; Pfarr et al, 2006; Ris-Stalpers and Bikker, 2010). However, none of the genes are specific to thyroid disorders (Cortés and Mendieta Zerón, 2019).…”
Section: Introductionmentioning
confidence: 99%